ROOTING IN FOREIGN SOIL: AN ANALYSIS OF HYBRIDITY AND DIASPORA IN FAMILY REPRESENTATION IN MINARI - Allysa Mutiara Sani; Yusrina Dinar Prihatika (Lire Journal (Journal of Linguistics and Literature), 2025)
This study investigates how Lee Isaac Chung’s film Minari (2020) represents cultural hybridity and diasporic identity negotiation within a Korean-American immigrant family in Arkansas. Using hybridity and diaspora theoretical frameworks, this research addresses how Yi family balances preservation of Korean cultural heritage with adaptation to American societal norms. Through semiotic and narrative analysis, the study finds that Minari portrays hybrid identity formation as a dynamic and intergenerational process characterized by both cultural retention and adaptation. It reveals familial conflicts and solidarities that highlight differing aspirations-such as Jacob’s pursuit of the American Drea, balanced against the family’s Korean heritage, and Monica’s emphasis on familial cohesion. The diaspora community emerges as a crucial space for articulating multifaceted identities and supporting resilience amid economic and social challenges. These findings illustrate how Minari critically engages with immigrant experiences, offering nuanced insight into identity negotiation beyond assimilation paradigm.